Resilience evaluation of industry and supply chains of clean energy metals in China - LAN Tingting, SHAO Liuguo (Ziyuan Kexue)
[Objective] A systematic evaluation of the resilience of China's industry and supply chains of clean energy metals to identify weaknesses and bottlenecks that impede resilience enhancement is crucial for ensuring the security of clean energy industry and supply chains and facilitating energy transition and technological innovation in China. [Methods] Integrating strategic priorities of industry and supply chain resilience and the unique characteristics of industry and supply chains of clean energy metals, this study established an evaluation indicator system with 12 indicators across four dimensions: control capacity, competitiveness, collaborative capacity, and geopolitical cooperation capacity. Using entropy weight method and TOPSIS-grey relational analysis, this study evaluated the resilience levels of China's industry and supply chains of clean energy metals from 2018 to 2022, with copper, aluminum, lithium, and cobalt as examples. [Results] (1) The overall resilience level of China's industry and supply chains of clean energy metals remained relatively low, showing a continuous downward trend before 2021 and an upward trend in the post-pandemic recovery period since 2021. Resilience levels varied significantly among different mineral types and supply chain segments. Emerging minerals outperformed bulk minerals, and processing/manufacturing and smelting demonstrated significantly higher resilience than upstream mining. (2) Bottlenecks and weaknesses hindering resilience enhancement of China's industry and supply chains of clean energy metals were identified. Insufficient industry integration impeded rapid and efficient coordination with other segments. Failure to effectively control international market shares limited control capacity. R&D investments by related enterprises were declining, particularly in bulk mineral-dominated industries lacking new growth drivers, making the lack of R&D investment a more prominent barrier. The barrier caused by insufficient geopolitical cooperation capacity was increasing. Emerging minerals such as lithium and cobalt in upstream segments were more affected, while bulk minerals such as copper and aluminum in mid-to-downstream segments were more affected. [Conclusion] China's industry and supply chains of clean energy metals show low resilience levels due to insufficient integration across the whole industry chain, insufficient international market shares, weak investment momentum, and declining geopolitical cooperation capacity. To enhance the resilience of industry and supply chains of clean energy metals, China should promote integrated development of industry and supply chains, leverage its ultra-large domestic market to establish first-mover advantages in market control. Enterprises, particularly those in the mid-to-downstream segments, should be incentivized to increase R&D expenditures, while a combination of centralization and diversification strategies should be adopted to develop collaborative global supply chain networks.